A institucionalização de interesses organizados na agenda do Estado no Brasil e na Argentina em perspectiva comparada: o caso do futebol (1930-2020) - Nascimento, Jefferson Ferreira do (Universidade Federal de São Carlos, 2022)
The objective of this thesis was to verify how the process of political institutionalization of organized soccer interests in Brazil and Argentina took place, based on historical neo-institutionalism and the path dependence. For this, we carried out bibliographic and documentary analysis on the period 1930-2020 using the Comparative Process Tracing (CPT) method. The information was organized in critical junctures and focal points, and the analysis was carried out intra-cases and between-cases. For Brazil, we conducted semi-structured interviews with former deputy Silvio Torres and journalist Juca Kfouri. The limitations imposed by the Covid-19 pandemic made it impossible to contact Argentine politicians and journalists for interviews. The interviews allowed greater detail and comparison of the image produced by the research with the impressions of qualified observers of the analyzed phenomenon, but they do not support inferences and conclusions in isolation. We argue that an institutionalization process initiated before the party system raises the costs of breaking the trajectory, tending to institutional changes by layering. As a result, we identified that the set of football entities was configured as an informal political institution in both countries. The entry of organized football interests into the state agenda is related to the crisis of liberalism. However, there are specificities: the dispute between Brazilian soccer managers and the labor mobilization of the Argentine players provoked conflicts considered deleterious. The Argentine concentric arrangement potentiated the effects of the context of the Buenos Aires metropolitan region, bringing the influence of urban conflicts to soccer matters; the Brazilian polycentric arrangement shifted conflicts to intra-elite disputes. Thus, the entry of the State on the scene occurs at the same time, under different justifications and generated consequences that are still present today: the relative importance of championships and regional classics in Brazil; the mobilization capacity of Argentine players and the concentration of the main clubs in Buenos Aires and surroundings. Another distinctive point is the institutional design: Federalism institutes intergovernmental relations that, together with the party system's ability to channel demands, impact the way interests are organized and inserted into the political system. In Brazil, this resulted in strategies for acting in the Legislature in the post-redemocratization period – see the formation of the “bancada da bola”. In Argentina, interests depend on the participation of provincial leaders and action on the Federal Executive.

El objetivo de esta tesis fue verificar cómo se produjo el proceso de institucionalización política de los intereses del fútbol organizado en Brasil y Argentina, a partir del neoinstitucionalismo histórico y el modelo de causalidad social dependiente de la trayectoria. Para ello, realizamos análisis bibliográfico y documental sobre el período 1930-2020 utilizando el método de Trazado Comparativo de Procesos (CPT). La información se organizó en coyunturas críticas y puntos focales, y el análisis se realizó intracaso e intercaso. Para Brasil, realizamos entrevistas semiestructuradas con el exdiputado Silvio Torres y el periodista Juca Kfouri. Las limitaciones impuestas por la pandemia del Covid-19 imposibilitaron contactar a políticos y periodistas argentinos para entrevistas. Las entrevistas permitieron mayor detalle y comparación de la imagen producida por la investigación con las impresiones de observadores calificados del fenómeno analizado, pero no sustentan inferencias y conclusiones en forma aislada. Argumentamos que un proceso de institucionalización iniciado antes del sistema de partidos eleva los costos de romper la trayectoria, tendiendo a cambios institucionales por capas. Como resultado identificamos que el conjunto de entidades futbolísticas se configuró como una institución política informal en ambos países. La entrada de los intereses del fútbol organizado en la agenda estatal está relacionada con la crisis del liberalismo. Sin embargo, hay especificidades: la disputa entre los dirigentes del fútbol brasileño y la movilización laboral de los jugadores argentinos provocaron conflictos considerados perjudiciales. El arreglo concéntrico argentino potenció los efectos del contexto de la región metropolitana de Buenos Aires, trayendo la influencia de los conflictos urbanos a los asuntos futbolísticos; el arreglo policéntrico brasileño desplazó los conflictos a disputas intra-élite. Así, la entrada del Estado en escena ocurre al mismo tiempo bajo diferentes justificaciones y generó consecuencias que aún hoy están presentes: la importancia relativa de los campeonatos y clásicos regionales en Brasil; la capacidad de movilización de jugadores argentinos y la concentración de los principales clubes en Buenos Aires y alrededores. Otro punto distintivo es el diseño institucional: el federalismo instituye relaciones intergubernamentales que, junto con la capacidad de canalización de demandas del sistema de partidos, impactan la forma en que los intereses se organizan e insertan en el sistema político. En Brasil, esto resultó en estrategias para actuar en la Legislatura en el período posterior a la redemocratización – ver la formación del “banco de pelota”. En Argentina, los intereses dependen de la participación de los mandatarios provinciales y de la acción del Ejecutivo Federal.
The institutionalization of organized interests in the State agenda in Brazil and Argentina in a comparative perspective: the soccer case (1930-2020)
La institucionalización de los intereses organizados en la agenda del Estado en Brasil y Argentina en una perspectiva comparada: el caso del fútbol (1930-2020)
Keywords: Brasil; Argentina; Institucionalismo Histórico; Futebol; Sistema Político; Brazil; Argentina; Historical Institutionalism; Soccer; Political System; Brasil; Argentina; Institucionalismo Histórico; Fútbol; Sistema Político; CIENCIAS HUMANAS::CIENCIA POLITICA::ESTADO E GOVERNO